" Life is not a problem to be solved but a reality to be experienced! "
© Copyright 2013 - 2025 KUDO.TIPS - All rights reserved.
5x +7 -4x +8 = 7 -x
5x -4x +x = 7 -7 -8
2x = -8
x = -8/2
x = -4
b) 4 (x - 5) - 1 = 3 (x - 2)
4x -20 -1 = 3x -6
4x -3x = -6 +20 +1
x = 15
c) 3 (x - 5) - 2 (x + 4) = 18
3x -15 -2x -8 = 18
3x -2x = 18 +15 +8
x = 41
5x +7 - 4 (x - 2) = 7 - x
5x +7 -4x +8 = 7 -x
5x -4x +x = 7 -7 -8
2x = -8
x = -8/2
x = -4
Solución :
x = -4
b)
4 (x - 5) - 1 = 3 (x - 2)
4x -20 -1 = 3x -6
4x -3x = -6 +20 +1
x = 15
Solución :
x = 15
c)
3 (x - 5) - 2 (x + 4) = 18
3x -15 -2x -8 = 18
3x -2x = 18 +15 +8
x = 41
Solución :
x = 41